Case report Scleromyxoedema in a 70-year-old woman – case report and review of the literature - Maciejewska-Radomska, Agata; Sokołowska-Wojdyło, Małgorzata; Wilkowska, Aleksandra; Michajłowski, Igor; Roszkiewicz, Jadwiga (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Lichen myxoedematosus and its generalized papular and sclerodermoid form is a rare, chronic scleroderma-like disease. Skin thickening with concomitant lichenoid papules dominates in the clinical picture. Papules tend to disseminate on the hands, forearms, face, back, trunk and thighs. Pruritus is a very common symptom in the course of the disease. Furthermore, sclerodactyly may appear as well as scleroderma-like skin changes on the face. In some cases monoclonal gammopathy is also observed. In general, the treatment of scleromyxoedema is disappointing, especially because of visceral involvement. We present the case report of a 70-year-old woman with scleromyxoedema treated with melphalan ineffectively.